FAKTOR ESKTRINSIK DAN INTRINSIK YANG MEMPENGARUHI PERILAKU GREEN CONSUMER DI BEBERAPA NEGARA - Priscilia, Melvina (Fakultas Ekonomi Universitas Wisnuwardhana, 2016)
Abstract: Today, healthiness and environmental problem hasbecame people’s attention around the world. The impact of damagedenvironment can seem clearly. Environmental problem is closelyrelated to healthiness problem. Nowadays, some countries have donesome efforts to reduce the environmental and healthiness problem.Recently, Green consumer behavior becomes a major focus becauseit can be the solutions to minimize environmental and healthinessproblems. Most people begin to realize the behavior of environmentalcare and change their habit include usage habits of goods. The societybegin to switch to consume green product as their efforts to minimalizenegative impact of the consumption of products. Motivation have animportant role to affected society’s behavior. Obviously, the society’sbehavior in every country in green consumer behavior are different.That motivation then affect the purchasing decisions for consumers. Obviously, creating the motivation of marketing’srole is an important thing.Keywords: Buying Decision Making; Evironment; Green Consumer;Motivation